Religious capital and religious participation in New Eastern Europe - Сальнікова, Світлана Анатоліївна; Решетняк, Олена; Миронович, Дмитро; Сальникова, Светлана Анатольевна; Решетняк, Елена; Миронович, Дмитрий; Salnikova, Svitlana; Reshetnyak, Olena; Myronovych, Dmytro (Київський національний університет імені Тараса Шевченка, Open Society Institute (Будапешт), 2012)
The article will introduce current definitions of social and religious capital, examples of how this concept can be applied in the investigation of religious commitment and religious participation. According to the theory of social capital by J.Coleman, R.Putnam and P.Bourdieu, religious participation has direct influence on: membership in correspondent religious organizations, the activity of which is spread out over the area civil society and where the effect of religious involvement is the most powerful; affiliation to wider range of non-religious civil organizations and associations. The authors try to identify the relations hip between religious participation and civil activity in NEE and EU’s countries. The investigation employs of European Values Survey (2008) and World Value Survey dates (2005, 2008). The results indicate the weak correlation between religious participation and affiliation to wider range of non-religious civil organizations and associations in Ukraine, Russia and Moldavia. Religious capital as a symbolic resource of legitimation is also considered in the article in the perspective of religious schisms with the focus on the mechanisms of reconstruction of the religious field. Religious capital as a tool of mobilization of different social groups is a desirable resource for political powers. This perspective is adopted for the investigation of the religious capital production in the situation of the religious schisms in the NEE countries. В статье представлено применение понятий социального и религиозного капиталов в исследовании религиозной приверженности и участия. Исследование основывается на теории социального капитала Дж.Коулмена, Р.Патнема и П.Бурдье. Предлагается анализ влияния религиозного участия в гражданском обществе, а также участия в нерелигиозных организациях и объединениях; определяется зависимость между религиозным участием и гражданской активностью в странах Новой Восточной Европы и Европейского Союза. В качестве эмпирических данных использованы данные Европейского исследования ценностей (2008) и Мирового исследования ценностей (2005, 2008). Результаты анализа указывают, что существует слабая корреляция между религиозным участием и принадлежность к более широкому кругу нерелигиозных организаций и объединений в постсоветской Украине, России и Молдове в отличие от стран ЕС. Религиозный капитал как символический ресурс легитимации власти и реконструкции религиозного пространства анализируется в перспективе формирования религиозных расколов. Эта перспектива адаптирована к исследованию производства православного религиозного поля под влиянием религиозных расколов в постсоциалистических Украине, Болгарии и Молдове. У статті представлено застосування понять соціального і релігійного капіталів у дослідженні релігійної прихильності та участі. Дослідження ґрунтується на теорії соціального капіталу Дж.Коулмена, Р.Патнема і П.Бурдьє. Пропонується аналіз впливу релігійного участі у громадянському суспільстві, а також участі в нерелігійних організаціях і об'єднаннях; визначається залежність між релігійною участю і громадянською активністю в країнах Нової Східної Європи та Європейського Союзу. З метою емпіричного аналізу використано дані Європейського дослідження цінностей (2008) і Світового дослідження цінностей (2005, 2008). Результати аналізу вказують, що існує слабка кореляція між релігійною участю і приналежністю до більш широкого кола нерелігійних організацій та об'єднань в пострадянській Україні, Росії та Молдові на відміну від країн ЄС. Релігійний капітал як символічний ресурс легітимації влади і реконструкції релігійного простору аналізується в перспективі формування релігійних розколів. Ця перспектива адаптована до дослідження виробництва православного релігійного поля під впливом релігійних розколів в постсоціалістичних Україні, Болгарії і Молдові.
Релігійний капітал і релігійна участь в Новій Східній Європі
Религиозный капитал и религиозное участие в Новой Восточной Европе
Keywords: social capital; социальный капитал; соціальний капітал; religious capital; религиозный капитал; релігійний капітал; religious participation; религиозное участие; релігійна участь; schism; раскол; розкол; field of religion; поле религии; поле релігії; civil society; гражданское общество; громадянське суспільство; civil associations; гражданские ассоциации; громадянські асоціації